INTEGRATED BASEMENT : MENCIPTAKAN BASEMEN RAMAH LINGKUNGAN DENGAN LAHAN PARKIR YANG BERTEKNOLOGI TINGGI. - Wahyudimar, Gigih Etqi (Jurnal Proyek Teknik Sipil, 2020)
According to data from the Indonesian Central Agency of Statistic, there are 708 shopping centers (malls) in Indonesia in 2018, this figure is equivalent to 4.45% of the total trade centers in Indonesia. The basic meaning of the shopping center is a public area that connects every store with the society. Based on the theory of Ray Oldenburg, an urban sociologist from the United States, “People spend the majority of their lives in one of three places. The first is the home, the second is the workplace, and the third is any other social space”. The shopping center is one part of “the third places”, people spend their time doing economics transactions or just relaxing in the shopping center. So that with the  massively increasing development of shopping centers in Indonesia, it is need a construction design and building manage that more creative and based on eco-technology also maximize the “internet of things” as part of building operations. “Integrated Basement : Creating an Eco-Technology Basement with High-Tech Parking Area” is the main focus for the writer to design the basement as an underground building area that often used as a parking area to be a “smart parking area” and “green area” by focusing on how the building operations become efficient, environmentally friendly and high-tech integrated. Smart parking area also means that the basement be an area that can interact and be able to adapt to shopping center’s visitors. With this planning, hoped that urban society can enjoying the shopping centers as public area that environmental friendly, comfortable, also efficient and integrated.